Pengembangan Produk Pangan Lokal untuk Pencegahan Stunting Sebelum Genting di Dusun Karang Keting, Desa Karangsono Kabupaten Jember - Rofi Hidayah, Anis; Wulan, Werdining; Lutfi ah, Hikmatul; ., Irfiah; Vitriyah, Nurul Lailatul (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
The quality of human resources in the future will be influenced by stunting. One goal set in relation to sustainable development (SDG) is stunting. Posyandu in Karangsono Village are actively held evenly throughout the village. However, in Karangsono Village, especially in Karang Keting Hamlet, there are still cases of stunting. Therefore, the Jember Islamic University Service Team held outreach with the aim of educating the community to increase knowledge about stunting related to parenting patterns and meeting children's nutritional needs at Posyandu Mangga 136 Karang Keting Hamlet. The activity to deliver material on preventing stunting was carried out on August 5, 2023, attended by 30 participants consisting of pregnant women, mothers with children under five and mothers of childbearing age. Mothers' knowledge about nutritional adequacy from the womb to the first 1000 days of life is very important. With the right knowledge, mothers can also prevent stunting in children. However, many people consider nutritious food to be synonymous with expensive prices. Even though nutritious food sources can be obtained easily and can be cultivated independently or together. Fulfilling nutrition for children and toddlers to avoid stunting is the obligation of all family members, not just the mother's duty. For this reason, further outreach is needed to other family members so that they always become a support system for mothers and children so that they can avoid stunting.